Social entrepreneurship and corporate sustainable development. Evidence from Vietnam - Nguyen Hoang Tien; Ho Thien Thong Minh; Le Doan Minh Duc; Nguyen Phuong Mai; Tran Duy Thuc (Cogent Business & Management, 2020)
This article investigates the concepts and issues of social enterprise, social entrepreneurship, their sustainability and strategic dimension. Regarding the current two contradictory forms of entrepreneurship (commercial and social entrepreneurship) in terms of their nature, motivation, purpose and orientation toward sustainable development, this research shows that both of them could to stay in an alliance to successfully bridge social and commercial capital for corporate sustainable development and social sustainable development. However, the article revealed that in contrast to the commercial entrepreneurship, currently, social entrepreneurship, due to higher level of sophistication, lacks and needs more strategic approach and understanding as well as its full reflection not only in theoretical debates but also in the business reality. This way, enterprises and society could benefit from it in terms of supporting overall sustainable development in rural areas of Vietnam. Finally, the article proposed some feasible solutions to enhance strategic impact of social entrepreneurship and promote its further expansion for the purpose of sustainable development.
Keywords: 650; sustainable entrepreneurship; social entrepreneurship; social enterprise; sustainable development; Vietnam